Factorial analysis of psychological and technical-tactic fitness of tennis players at stage of specialized basic training - Makuts, T.B.; Vysochina, N.L. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2015)
Purpose: determination of structure of psychological and technical-tactic tennis players’ fitness by method of main components. Material: in the researches 24 tennis players of 14-15 years old age participated. For determination of personalities’ psychological components of junior tennis players the following methodic were used: Dembo- Rubinstein’s (self assessment), Burdon-Anfimov’s (attention), test by G. Izenko (type of temper), T.Elers’s (motivation), Sbilberger-Khanin’s (level of anxiety). Results: we have determined the structure of psychological and technical-tactic fitness of tennis players at stage of specialized basic training. For psychological fitness it was determined five factors, for technical-tactic fitness - three. High level of inter-factor interconnections was observed only if structure of technical-tactic fitness. Between five factors of psychological fitness we did not find any significant links. Conclusions: the determined peculiarities of factorial structure of tennis players’ fitness can be used for planning of psychological training programs and in the training process of junior tennis players.